Management of Fractured Endodontic Instruments A Clinical Guide (Springer International Publishing, 2018)
This superbly illustrated book provides detailed information on the causes of instrument failure during endodontic treatment, the factors influencing the management of such cases, and the diverse management options that may be employed to resolve the problem. Readers will find clear descriptions and comparative evaluation of the available methods, techniques, and devices. Complications that may arise during the management of fractured instruments are described, and the impact of retained file fragments on the prognosis of endodontic treatment is discussed. In addition, means of preventing iatrogenic errors from occurring in the first place (the best form of management) are explained, emphasizing that the risk of instrument failure is reduced if proper guidelines are carefully considered and followed. The book will assist both endodontists and general dental practitioners in achieving an optimal outcome when confronted with the time-consuming and challenging task of dealing with a fractured instrument within the root canal - a still frequent circumstance despite the plethora of improvements in instrument design, alloy composition, and manufacturing processes.